Paralympic athletes` perceptions of their experiences of sports-related injuries, risk factors and preventive possibilities - Fagher, K.; Forsberg, A.; Jacobsson, J.; Timpka, T.; Dahlström, Ö.; Lexell, J. (European Journal of Sport Science, 2016)
Our knowledge of sports-related injuries in para-sport is limited and there are no data on how Paralympic athletes themselves perceive an injury. The aim of this qualitative study was to explore Paralympic athletes` perceptions of their experiences of sports-related injuries, risk factors and preventive possibilities. Eighteen Swedish Paralympic athletes with vision impairment, intellectual impairment, spinal cord injury, cerebral palsy, myelomeningocele, dysplasia and neuromuscular disorder, representing 10 different para-sports, were interviewed. The qualitative phenomenographic method was used to interpret the data. The analysis revealed nine categories of perceptions of experiences. The athletes perceived that their impairments were involved in the cause and consequential chains associated with a sports-related injury. Other categories that denoted and described these injuries were: sport overuse, risk behaviour, functional limitations, psychological stressors, the normalised pain, health hazards, individual possibilities to prevent sports-related injuries and unequal prerequisites. This qualitative study revealed that Paralympic athletes` perceptions of their experiences of sports-related injuries are complex and multifactorial, and in several ways differ from able-bodied athletes. This needs to be considered in the sports health and safety work within the Paralympic Movement as well as in the design of future injury surveillance systems and preventive programmes